Le Theater Meschugge (Móin-Móin - Revista de Estudos sobre Teatro de Formas Animadas, 2018)
This paper analyzes the artistic route and the creative process of five presentations of Ilka Schönbein –Theater Meschugge: The Old One and the Beast – to my father; The Silence of the Goats; Metamorphosen; Winter Journey; and My Own Flesh and Blood. The analysis of the presentations is completed with the transcription of an interview and of theatrical reviews of her work published in French newspapers and magazines, which provide a more complete dimension of the artistic production of the actress and director.Keywords: Theater Meschugge. Ilka Schönbein. Theatrical staging. Creative process.